Bolnik z vročino, izpuščajem, bolečinami za očmi in razjedami v ustih po vrnitvi iz Kenije - Trampuž, Andrej (Medicinski razgledi, 2000)
The paper describes a case of a 52-year-old patient who presented with a high fever, fatigue, myalgia, retrobulbar headache, a confluent maculopapular rash,conjunctivitis and oral ulcers four days after his return from Kenya. Theblood film showed mild leukopenia with a shift to the left, mild thrombocytopenia and elevated hepatic aminotransferases about twu times the normal values. Three consecutive thick blood films showed no malaria parasites. Salmonella heidelberg was isolated from stool cultures. The patientwas immediately admitted to the hospital under suspicion of dengue.
Keywords: Hiv infections; Diagnosis; Hiv seropositivity; Travel; Middle age; Kenya; Diagnosis, differential; diagnostika; HIV